Atypical leishmaniasis: A global perspective with emphasis on the Indian subcontinent. - Lovlesh Thakur; Kiran K Singh; Vinay Shanker; Ajeet Negi; Aklank Jain; Greg Matlashewski; Manju Jain (Public Library of Science (PLoS), 2018)
BACKGROUND:Among the neglected tropical diseases, leishmaniasis continues to be prevalent in many tropical and subtropical countries despite international, national, and local efforts towards its control and elimination over the last decade. This warrants a critical evaluation of such factors as under-reporting, asymptomatic infections, post kala azar dermal leishmaniasis (PKDL) cases, and drug resistance. In this review, we highlight lesser-understood atypical presentations of the disease involving atypical parasite strains against a background of classical leishmaniasis with a focus on the Indian subcontinent. METHODS AND FINDINGS:A literature review based on endemic areas, the nature of disease manifestation, and underlying causative parasite was performed with data collected from WHO reports for each country. Searches on PubMed included the term ''leishmaniasis" and "leishmaniasis epidemiology" alone and in combination with each of the endemic countries, Leishmania species, cutaneous, visceral, endemic, non-endemic, typical, classical, atypical, and unusual with no date limit and published in English up to September 2017. Our findings portray a scenario with a wider distribution of the disease in new endemic foci, with new discoveries of parasite-driven atypical disease manifestations in different regions of the world. Unlike the classical picture, some Leishmania species are associated with more than one disease presentation, e.g., the L. donovani complex, generally associated with the visceral form, is now also associated with a cutaneous disease presentation, while L. tropica species complex, known to cause cutaneous disease, can cause viscerotropic disease. This phenomenon points towards the discovery of novel parasite variants as etiologic agents of atypical disease manifestations and represents an excellent opportunity to identify and study genes that control disease virulence and tropism. CONCLUSIONS:The increased recognition of atypical leishmaniasis as an outcome of parasite variants has major implications for leishmaniasis control and elimination. Identifying molecular correlates of parasite isolates from distinct regions associated with different disease phenotypes is required to understand the current epidemiology of leishmaniasis in regions with atypical disease.